(untitled) (Praxis Educativa, 2020)
The objective of this work is to share an academic writing experience at the postgraduate level to bring to light the importance that peer groups and emotions play in the dissertation writing process. We consider that the bonds that are constructed in these groups improve academic writing since they offer emotional and academic support. Taking into account the problem of low graduation rates at the postgraduate level, we believe that a possible explanation is that academic work is mostly associated with an individual activity. We conclude that encouraging initiatives such as the writing groups equals to start thinking and embodying other academic trajectories, where experiences that celebrate and embrace peer work become a key component of new ways of becoming a researcher.